Transparency in government operations - Kopits, George (IMF WashingtonUS, 1998)
Focuses on two dimensions of fiscal transparency viz. the provision of reliable informatin of the government's fiscal policcy intentions and forecasts; the provision of detailed data on government operaations. Seeks to identify specific practices e.g. trnsparency in fiscal statistics and targets as well as budget and tax collection procedures that enhance good governance through greater visibility to the public.